Early Childhood Multicultural Education in the Islamic Sharia Area - Tamwifi, Irfan; Zulkarnain; Akbar, Eliyyil; Abidah (JURNAL PENDIDIKAN USIA DINI, 2023)
Cases encountered in the field related to intolerance in early childhood include children making fun of each other regarding social status, cultural differences, religious differences, skin color, and dialect differences. Early childhood in the field of Islamic law is prone to conflict problems. The purpose of this writing is to describe multicultural learning practices in areas of Islamic law. The method used is field research with a qualitative approach. The result of this writing is the implementation of multicultural learning at early childhood education institutions in Budidharma Kindergarten, Central Aceh Regency through the integration of multicultural values. The implementation of multicultural learning in early childhood education institutions at Budidharma Kindergarten also covers all aspects of child development, namely cognitive, moral, religious, physical-motor, socio-emotional, language, and arts. Keywords: Learning, Multicultural, Islamic Sharia References: Abdullah, Irwan. 2010. “Berpihak Pada Manusia: Paradigma Nasional Pembangunan Indonesia Baru.” In , 21. Yogyakarta: Pustaka Pelajar. Anggito, Albi, E. Kus Eddy Sartono, Ali Mustadi, Nada Savitri Nawangsari, and Astri Widyasari. 2022. “Effectiveness of Multicultural-Based Comic to Improve Learning Achievement and Tolerance Characters in Elementary School.” Proceedings of the 5th International Conference on Current Issues in Education (ICCIE 2021) 640 (Iccie): 275–80. https://doi.org/10.2991/assehr.k.220129.050. Arikunto, S. 2006. Metode Penelitian Kualitatif. Bumi Aksar. Jakarta. Budiono, Arief, Adi Dharmawan Muhammad, Fatimah Az, Zahra Atmoko, Sheryn Marsya, Azzah Aslika, Waskito Budi Kusumo, Dimas Wegig, Tri Hartanto, and Muhammad Qawiyyul Amin. 2022. “Policy for Implementation of Islamic Law Under Special Autonomous Province.” International Journal of Multicultural and Multireligious Understanding 9 (3): 626–36. Fadlilah. 2017. “Model Kurikulum Pendidikan Multikultural Di Taman Kanak-Kanak.” Jurnal Pembangunan Pendidikan; Fondas5 (1): 42–51. Heale, Roberta, and Dorothy Forbes. 2013. “Understanding Triangulation in Research.” Evidence-Based Nursing 16 (4): 98. https://doi.org/10.1136/eb-2013-101494. Lestari, Ambar Sri. 2015. “Penerapan Pembelajaran Multikultural Berbasis Teknologi Dengan Pendekatan Konstruktivisik.” Zawiyah Jurnal Pemikiran Islam 1 (1): 59–78. https://ejournal.iainkendari.ac.id/index.php/zawiyah/article/view/401. Mahmud, Choirul. 2009. “Pendidikan Multikultural.” In Cet.2, 176. cet. 3, (Yogyakarta: Pustaka Pelajar. Mariadi. 2018. “Pelaksanaan Syariat Islam Pada Qanun Nomor 11 Tahun 2002 Bidang Aqidah, Ibadah, Dan Syiar Islam.” Legalite : Jurnal Perundang Undangan Dan Hukum Pidana Islam 3 (II): 113–54. https://doi.org/10.32505/legalite.v3iii.1106. Masruroh, Imas, Siti Badriah, Mohamad Erihadiana, and Uus Ruswandi. 2022. “Multicultural Curriculum Development and Learning Model at the Ta’lim Sakinah Majelis.” Edukasi 16 (1): 35–46. https://doi.org/10.15294/edukasi.v16i1.37993. Mazurkiewicz, Piotr. 2020. “Cultural Diversity versus Multiculturalism.” Chrześcijaństwo-Świat-Polityka, no. 24: 229–50. https://doi.org/10.21697/csp.2020.24.1.29. Mo’tasim, Mo’tasim, Moh. Kalam Mollah, and Ifa Nurhayati. 2022. “Konsep Pendidikan Multikultural Dalam Pandangan Banks.” FIKROTUNA: Jurnal Pendidikan Dan Manajemen Islam 15 (01): 72–90. https://doi.org/10.32806/jf.v15i01.5863. Nurohma, Nyimas. 2017. “Strategi Pengembangan Kegiatan Keagamaan Anak Usia Dini Di Tk Harapan Ibu Tanah Mas Banyuasin.” El-Ghiroh Vol. XIII,: 108–29. Prabowo, Alfian Dewan Adhayuda, and Hamim Ilyas. 2021. “Multicultural Education in Islamic Perspective.” Proceedings of the International Conference on Economics, Business, Social, and Humanities (ICEBSH 2021) 570 (Icebsh): 371–76. https://doi.org/10.2991/assehr.k.210805.060. Primawati, Laurencia. 2013. “Dosen FISIPOL Universitas HKBP Nommensen Medan JUPIIS VOLUME 5 Nomor 2, Desember 2013 82” 5: 82–92. Rachmawati, Y., Pai, Y. F., & Chen, H. H. 2014. “The Necessity of Multicultural Education in Indonesia.” International Journal of Education and Research, no. October 2014. Rahim, Rahmawaty. 2012. “Signifikansi Pendidikan Multikultural Terhadap Kelompok Minoritas.” Analisis XII: 161–82. Retnowati, May Shinta, Musta’an Al Faruqi, and Syahrul Ihsan. 2023. “The Sources of Islamic Law on the Muamalah Concept About Contract Viewed on Philosophical Studies.” Al-Iktisab: Journal of Islamic Economic Law 7 (1): 75–94. https://doi.org/10.21111/aliktisab.v7i1.9961. Riyanto, Yatim. 2012. “Paradigma Baru Pembelajaran.” In , 163. Jakarta: Kencana Prenada Media. Group. Suri, Dharlinda, and Dharnita Chandra. 2021. “Teacher’s Strategy for Implementing Multiculturalism Education Based on Local Cultural Values and Character Building for Early Childhood Education.” Journal of Ethnic and Cultural Studies 8 (4): 271–85. https://doi.org/10.29333/ejecs/937. Sutarto, Joko. 2016. “Pentingnya Pembelajaran Multikultural Pada Pendidikan Anak Usia Dini.” Edukasi, no. 3: 1–13. Wihardit, Kuswaya. 2010. “Pendidikan Multikultural: Suatu Konsep, Pendekatan Dan Solusi.” Jurnal Pendidikan 11 (2): 96–105. http://jurnal.ut.ac.id/index.php/JP/article/view/98. Yanuari Dwi Puspitarini, and Muhammad Hanif. 2019. “Using Learning Media to Increase Learning Motivation in Elementary School.” Anatolian Journal of Education 4 (2): 53–60. https://doi.org/10.29333/aje.2019.426a.